Development and prospects of standardization in the German municipal wastewater sector: Version 1.0 - Claudia Freimuth; Mark Oelmann; Erwin Amann (Universität Duisburg-Essen, Institut für Betriebswirtschaft und Volkswirtschaft (IBES), 2018)
Given the significance of wastewater treatment and disposal for society and the economy together with the omnipresence of standards in the sector, we studied the development and prospects of the rules governing the formal standardization in the German municipal wastewater sector. We find that the German Association for Water, Wastewater and Waste (DWA) has significantly improved its rules on standardization over time by aligning them closer to the generally accepted superordinate standardization principles. However, by focusing on theoretical findings of committee decision-making and committee composition, we argue that there is still significant scope for improvement with respect to rule reading and rule compliance. We show that the incentives at work in standardization committees are manifold, whereas the representation of the different stakeholder groups needs' remains unbalanced. Due to vested interests and potential strategic behavior of the various agents involved in standardization rule compliance does not happen naturally. To this end, we claim that the implementation of monitoring or control mechanisms, respectively, can be a significant contribution to the institutional design of standardization and briefly discuss the advantages and disadvantages of external and internal monitoring. Finally, we show that there is ample need for future research on the optimal design of such a scheme. Even though the analysis relates specifically to the DWA our claims apply to a wide range of standards development organizations.
Keywords: 330